2020
DOI: 10.1155/2020/8882486
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Water Relations, and Photosynthetic Activity Are Associated with Evaluating Salinity Stress Tolerance of Wheat Cultivars

Abeer Hamdy Elhakem

Abstract: Salinity stress riskiness adversely affects the population by causing food and environmental issues. Moreover, the destructive impacts of salinization differ among various plant cultivars. In the present study, we evaluate the salt stress tolerance among three wheat cultivars based on growth criteria, leaf relative water content (LRWC), and abscisic acid (ABA) level by treating the plants with 0, 40, 80, or 160 mM NaCl. The results revealed that an increase in NaCl concentration caused a massive reduction in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
3
1
0
Order By: Relevance
“…However, tolerant accessions showed a lesser reduction percentage compared to sensitive ones. These results are in agreement with the findings of earlier studies [ 37 , 38 , 39 ] that reported a significant decrease in photosynthetic rate, transpiration rate, and chlorophyll content under salt stress. The decline in SPAD index under salinity may be due to photo-oxidation, loss of chloroplast membranes, and membrane injury in chloroplasts by ROS [ 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, tolerant accessions showed a lesser reduction percentage compared to sensitive ones. These results are in agreement with the findings of earlier studies [ 37 , 38 , 39 ] that reported a significant decrease in photosynthetic rate, transpiration rate, and chlorophyll content under salt stress. The decline in SPAD index under salinity may be due to photo-oxidation, loss of chloroplast membranes, and membrane injury in chloroplasts by ROS [ 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, disturbances in the turgidity of guard cells may be the possible reason for reduced transpiration and stomatal conductance under salt stress [ 50 ]. Similar to our findings, a significant reduction in net photosynthesis rate, transpiration rate, chlorophyll content, and stomatal conductivity was also reported in purslane, wheat, white willow, and eggplant [ 51 , 52 , 53 , 54 ], respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Water scarcity was found to be one of the most important factors in both predicting and regulating plant performance (Ahmad et al, 2023). To achieve maximum growth with optimal water availability, it is vitally important for plants to increase WUE (Elhakem, 2020). In the present study, Table 6 showed that compared to untreated plants; drought induced an additional reduction in RWC%, WUEG and a marked increase in SWD during heading.…”
Section: Response Of Water Relations To Drought and K Applicationsupporting
confidence: 51%